MENGEMBANGKAN PENALARAN INDUKTIF SISWA MELALUI MODEL PEMBELAJARAN 5E PADA SISWA KELAS X SMAN - Nurfitriany Fakhri; Amirah Aminanti Agussalim; Abiyyu Arib Mahyiyuddin; Nabila Nurulfiqri; Sahril Buchori; Nurul Islamiyah (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
Inductive reasoning skills must be trained and incorporated into the learning process. The purpose of this community service activity is to develop a learning model using the 5E model technique in improving the inductive reasoning skills of SMAN 1 Gowa students. The results of this activity show that the learning model developed with the 5E model technique is suitable to be applied in the classroom. The 5E learning model can effectively improve the inductive reasoning ability of SMAN 1 Gowa students.